Technical Aspects and Tips and Tricks for Double Stent Retriever Thrombectomy - Grzegorz Marek Karwacki; Guillaume Marie; Alexander von Hessling (Neurointervention)
Randomized clinical trials have established the clinical efficacy of mechanical revascularization compared to drug therapy. Successful reperfusion in mechanical thrombectomy is achieved in 53% to 83% of cases, often requiring multiple thrombectomies, which can prolong procedure times and potentially lead to worse outcomes and higher complication risks. The current body of literature suggests that the first pass effect (FPE) is of paramount importance. To achieve a higher FPE, a double stent retriever (DSR) technique is becoming more popular. This publication shares our experience, challenges, and learning journey in implementing DSR in our department.